Chapter Una nuova svolta negli studi letterari: la convergenza tra computazione, cognizione ed evoluzione - Ciotti, Fabio (Moderna/Comparata, 2022)
Distant reading, an empirical and quantitative approach in literary studies proposed by Franco Moretti, has raised a lively debate and attracted criticisms from "traditional literary scholars." An important reason behind these criticisms is the need for solid theoretical foundations: distant reading is perhaps the first methodology in literary studies that do not include a specific theory of literature, an ontology of the literary. Much of the work in the field derives its theoretical frameworks from the literary theories of the twentieth-century tradition, based on the assumption that literary texts can be understood through reading and interpretation. A large-scale quantitative approach to literary and cultural phenomena is mainly incompatible with "the hermeneutic attitude" and traditional theories. Therefore, I propose a convergence with cognitive and bio-evolutionary approaches to literature and studies of cultural evolution and a shift from "interpretation" to "explanation" as the goal of computational literary studies.